A MULTI-SITE ANALYSIS OF THE HUMAN GUT MICROBIOME AND METABOLITES IN ASSOCIATION WITH AMBULATORY BLOOD PRESSURE. (April 2021) - Marques, Francine; Tsyganov, Kirill; Ribeiro, Rosilene; Gill, Paul; Nakai, Michael; Carrington, Melinda; Yiallourou, Stephanie; Muir, Jane; Head, Geoffrey A.; Kaye, David
Abstract : Objective: High blood pressure (HBP) is a major risk factor for cardiovascular disease (CVD) and the prevalence of both is higher in regional versus metropolitan areas. The gut microbiome has emerged as important contributor to HBP, however, the relationship between BP and specific gut microbes and their metabolites is unclear. Here we aimed to determine if specific gut microbes and key metabolites such as short-chain fatty acids (SCFAs) were associated with 24 h BP whether geographic differences exist in Australia. Design and method: We recruited 70 subjects from the community in metropolitan (n = 40) and regional (n = 30) locations in Australia. White coat hypertension was present in 6% and masked hypertension in 19% of the cohort, and 34% were hypertensive. We assessed office and ambulatory BP, dietary intake via food frequency questionnaire, gut metabolites by gas-chromatography, and gut microbiome by 16S sequencing. Results: Mean(±SD) 24 h mean arterial pressure was 90.5 ± 10mmHg, systolic BP 122.8 ± 14.9mmHg, and diastolic 74 ± 8.4mmHg. There was a positive correlation between plasma short-chain fatty acid butyrate and 24 h systolic (r = 0.31, P = 0.01) and diastolic BP (r = 0.29, P = 0.02), confirmed by logistic regressions adjusted for age, sex and BMI (P = 0.001). Fifty seven genus were significantly correlated with diastolic BP (r = 0.38–0.41) after adjustment for multiple comparisons (FDR < 0.1). Inverse Simpson index, a marker of alpha diversity, was negatively correlated with 24 h mean arterial pressure (r = -0.24, P = 0.04), being driven particularly by 24 h diastolic BP and day BP. There were no differences in alpha or beta diversity between metropolitan and regional areas. Participants from metropolitan areas, however, had significantly lower levels of total SCFAs, acetate and butyrate (P < 0.05) without having any differences in fibre intake. Conclusions: This is the first study to analyse BP as a continuous variable, suggesting it is associated with a less diverse gut microbiome, higher levels of butyrate, and several genus of gut bacteria. Further studies will need to determine a causal relationship for these associations. We did not find a gut microbial difference between metropolitan and regional participants, but the latter had lower levels of SCFAs, which could help explain their predisposition to hypertension and cardiovascular disease.